Odpowiedź :
Odpowiedź:
a) 4x+4-x= -5
3x= -5-4
3x= -9 /: 3
x= -3
b) -3x-3-x= 9
-4x= 9+3
-4x= 12 /:(-4)
x= -3
16-2x-27+3x=0
-11+x=0
x= 11
c) 3x-6-5x= 10
-2x= 10+6
-2x= 16 /:(-2)
x= -8
Szczegółowe wyjaśnienie:
Odpowiedź:
a) 4 ( x +1) -x= - 5
4x + 4 -x = - 5
3x= - 5 -4
3x= - 9 /:3
x= - 3
b) -3 ( x +1) -x= 9
-3x -3 -x= 9
-4x= 9 +3
-4x= 12 /*(-1)
4x= - 12 /:4
x= - 3
) 2 ( 8 - x ) - 3 ( 9-x)= 0
16 -2x - 27 +3x=0
-2x+3x= 27 -16
x= 11
c) 3 ( x-2) - 5x= 10
3x -6 -5x= 10
-2x= 10+6
-2x= 16 /*(-1)
2x= - 16 /:2
x= - 8
Szczegółowe wyjaśnienie:
/*(-1) mnożymy obie strony równania przez -1, jeśli x jest ujemny, bo musi być dodatni.